Estimation of structure, characterization and studying properties of novel CuNiSnSex nanocomposits - Muhamad L.Ali; Mohanad Q.Karem (Genius Journals, 2021)
CunisnSe nanocomposits were successfully synthesized in this study using the nanometric approach. It possesses a monoclinic structure and a hexagonal phase, according to XRD diffraction data. The tiny crystal size of CunisnSe causes the XRD line to expand. However, the comparison determined a significant number of grid ratios. The The agglomerated and circular rectangular configurations nanocomposit were confirmed by FESEM pictures. The optimal energy gap, according to optical characteristics, is 1.25 e v. whech aids the thermoelctric performence of material or sorbeants in solar call aplications
Keywords: Optical Properties; Electric Properties; XRD